2002
DOI: 10.1038/sj.leu.2402369
|View full text |Cite
|
Sign up to set email alerts
|

Antileukemia activity of perillyl alcohol (POH): uncoupling apoptosis from G0/G1 arrest suggests that the primary effect of POH on Bcr/Abl-transformed cells is to induce growth arrest

Abstract: In hematopoietic cells, the Bcr/Abl tyrosine kinase that is encoded by the Philadelphia chromosome translocation both stimulates proliferation and activates an anti-apoptotic program that is associated with a G2/M delay upon exposure to various apoptotic stimuli. We recently reported that the monocyclic monoterpene, perillyl alcohol (POH) selectively induces in Bcr/Abl transformed cells, G0/G1 arrest and apoptosis. Therefore, POH activates anti-proliferative and apoptotic pathways against which the Bcr/Abl kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
25
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 64 publications
2
25
0
1
Order By: Relevance
“…other important molecules involved in neovessel formation, like Ang1, do not directly stimulate endothelial cell growth but rather stabilize vascular networks by promoting endothelial cell survival (Papapetropoulos et al, 1999(Papapetropoulos et al, , 2000. POH has well-established cytostatic and apoptotic activities in a variety of mammalian cancer cells (Crowell, 1999;Burke et al, 2002;Clark et al, 2002). We also observed the induction of programmed cell death in the cancer cell lines used in our study.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…other important molecules involved in neovessel formation, like Ang1, do not directly stimulate endothelial cell growth but rather stabilize vascular networks by promoting endothelial cell survival (Papapetropoulos et al, 1999(Papapetropoulos et al, , 2000. POH has well-established cytostatic and apoptotic activities in a variety of mammalian cancer cells (Crowell, 1999;Burke et al, 2002;Clark et al, 2002). We also observed the induction of programmed cell death in the cancer cell lines used in our study.…”
Section: Discussionsupporting
confidence: 59%
“…Data from rodents have shown that tumor regression occurs when plasma levels of perillic acid and dihydroperillic acid reach 390 to 480 M and 110 to 230 M, respectively (Belanger, 1998;Crowell, 1999). Additionally, POH has a cytostatic and cytotoxic effect against a variety of cancer cell lines (Crowell, 1999;Burke et al, 2002;Clark et al, 2002). Treatment of pancreatic tumor cells with POH for 2 days results in a concentration-dependent decrease in cell proliferation, with IC 50 values of 290 and 480 M for the human and hamster cell lines, respectively.…”
mentioning
confidence: 99%
“…In addition to early findings that isoprenoids may inhibit posttranslational protein prenylation (Crowell et al, 1991;Ren et al, 1997), reported effects include induction of G 0 /G 1 cell cycle arrest (Yu et al, 1995;Miquel et al, 1998;Clark et al, 2002;Elegbede et al, 2003), increased apoptosis (Haug et al, 1994;Mills et al, 1995;Reddy et al, 1997;Stayrook et al, 1997;Ariazi et al, 1999;Rioja et al, 2000;Burke et al, 2002;Clark et al, 2002;Elegbede et al, 2003;Xu et al, 2004), transient G 2 /M phase arrest (Shi and Gould, 2002;Rajesh and Howard, 2003), inhibition of cholesterol biosynthesis (Ren and Gould, 1994;Peffley and Gayen, 2003), inhibition of angiogenesis (Loutrari et al, 2004), and increased sensitization to radiation and anticancer drugs (Samaila et al, 2004).…”
mentioning
confidence: 93%
“…1,2 Medical interest in this compound has been generated by several researches showing that POH has been able to demonstrate activity against a variety of tumor models, such as adenocarcinoma, brain, breast, colon, gliomas, leukemic cells, liver, lung, pancreas, prostate and skin. [2][3][4][5][6][7] However, the results of phase I and II clinical trials showed nausea, vomiting and loose stools identified as common toxicities with rare leukocytosis, thrombocytosis, lethargy, renal tubular degeneration with elevated serum creatinine and gastritis. [8][9][10] Chemotherapeutic agents harm healthy tissues, leading to systemic toxicity and adverse effects that greatly limit the maximum tolerated dose of anti-cancer drugs and thus restrict their therapeutic efficacy.…”
Section: Introductionmentioning
confidence: 99%